(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the benefit of using a mouthguard in patients intubated in the ICU to prevent oral injuries. Methodology: Integrative literary review with bibliographic search for scientific articles in the electronic databases PubMed, LILACS (Latin American and Caribbean Literature in Health Sciences) and Google Scholar, between the years 2013 and 2023. Results: 89 articles were found. After analyzing the titles and abstracts, 23 articles were pre-selected and read in full. Then, 15 articles were included in the present review. Conclusion: To prevent oral injuries, mouth guards are low-cost and effective measures. Therefore, the presence of the dentist in the multidisciplinary team within the hospital is essential, so that the patient receives comprehensive health care.